Mark 1.21-29a: literary and socioreligious Study - Mena Oreamuno, Francisco (2021)
The article studies the first exorcism story in the Gospel according to Mark 1.21-29a. The comparison of that brief account with other relevant texts of that time shows that Jesus was not an exorcist and for this reason we wonder what is the best way to understand the social type of Jesus. This type of work helps us see the Bible with new eyes and, consequently, modify many premises that we have and that cultivate fundamentalism.